Estudo retrospectivo dos fatores associados ao desenvolvimento de câncer em cães na região de Uberlândia, Minas Gerais, Brasil (2015-2020) - Silva, Elis Maressa Gonçalves da (2021)
Cancer is one of the leading causes of death in dogs worldwide. It is increasingly needed to understand the factors involved in its development. The reduction in the occurrence of cancer depends on the identification of modifiable risk factors. Animal cancer registries are essential to developing epidemiological studies to identify, understand and circumvent these factors. This study aimed to determine the occurrence of cancer and its developmental characteristics in dogs treated in one of the first veterinary oncology departments in the country. Tumors were classified under the International Classification of Oncology for Humans guidelines based on morphology and location. The frequency of tumors in dogs was described over six years. A total of 2,152 tumors were diagnosed, the most common were mammary tumors, the most frequent location was breast, and females were the most prevalent, small dogs size were more prevalent, and the average age was 9.59 years. Breast cancer and mast cell tumors are the two most frequently diagnosed neoplasms in dogs, being responsible for a high rate of morbidity and mortality in this species. A retrospective case-control study was conducted for these two categories of tumors. The variables analyzed were: weight, age, sex, breed, height, body condition, reproductive status, body score, nutritional habits, housing, and street access. The potential risk factors were selected by univariate analysis (p<0.25) before the multivariate forward binary logistic. Logistic regression identified age, reproductive status, and breed type as risk factors for mammary tumors. Female dogs presented a higher risk of mammary tumor development with the increasing age. Unspayed females and Yorkshire and Poodle breeds had a higher chance of developing mammary tumors. In addition, we identified overweight, reproductive status and breed as possible risk factors for the development of mast cell tumors. Spayed dogs have a higher risk of developing mast cell tumors compared to unspayed dogs, we also found this higher risk associated with overweight dogs and Boxer breed dogs.